Psychological richness as a distinct dimension of well-being: Links to mental, social, and physical health - Naoki Konishi; Motohiro Kimura; Ken Kihara; Motoyuki Akamatsu; Minako Hosono; Fumie Sugimoto; Damee Choi; Kohei Fuseda; Toshihisa Sato (PLoS ONE, 2025)
In recent years, well-being research has expanded beyond traditional dimensions, recognizing that a fulfilling life may encompass more than happiness and meaning. We examined the unique contributions of a newly proposed dimension of well-being—psychological richness—to mental, social, and physical health outcomes alongside the established dimensions of hedonic and eudaimonic well-being. We assessed well-being using validated scales that measure life satisfaction, meaning in life, and psychological richness and analyzed data from 11,041 participants. We evaluated health outcomes across mental, social, and physical dimensions using the Subjective Well-being Inventory. Our findings revealed that life satisfaction and meaning in life consistently enhanced health outcomes across most domains. However, psychological richness exhibited a more nuanced profile. Specifically, psychological richness was strongly correlated with positive mental and social health indicators, such as confidence in coping and perceived social support, but also uniquely linked to social isolation and perceived physical symptoms. These results suggest that psychological richness fosters cognitive resilience and social engagement despite potential physical health and social connectedness trade-offs. Notably, individuals high in psychological richness did not report heightened negative emotions, even when experiencing social isolation or physical discomfort, aligning this dimension with other forms of well-being. This study identified psychological richness as an essential addition to well-being models, offering fresh perspectives for tailored well-being interventions.